Estimation of the Prevalence of Refractive Error in Kenya: A Systematic Review and Meta-Analysis. - Muma, Shadrack; Naidoo, Kovin; Hansraj, Rekha (Optometry & Visual Performance, 2023)
Purpose: To conduct a systematic review and meta-analysis on the prevalence of uncorrected refractive error in Kenya. Methods: This was a systematic review and meta-analysis of published papers extracted from PubMed and Google Scholar published between the years 2000-2022. A Boolean operator of "AND" and "OR" was used. A meta-analysis was carried out to estimate the prevalence of uncorrected refractive error in Kenya. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was applied in reporting systematic review and meta-analysis. Results: Out of the 20 identified articles, only eight were eligible for data extraction. The sample sizes varied from 326 to 10,579 in the eight articles. The prevalence of refractive error in Kenya reported from the meta-analysis was 6.39% (95% CI 2.3-7.2). The meta-analysis, using the random effect model, showed that sample size was statistically associated with the mean prevalence of refractive error per article (p=0.004). Conclusion: The prevalence of uncorrected refractive error continues to pose a major challenge with the growing population in Kenya. As a result, there is a dire need for up-to-date information from population-based studies on refractive error across all age groups.